A Large Scale Systemic RNAi Screen in the Red Flour Beetle Tribolium castaneum Identifies Novel Genes Involved in Insect Muscle Development. - Schultheis, Dorothea; Weiskopf, Matthias; Schaub, Christoph; Ansari, Salim; Dao, Van Anh; Grossmann, Daniela; Majumdar, Upalparna; Hakeemi, Muhammad Salim; Troelenberg, Nicole; Richter, Tobias; Schmitt-Engel, Christian; Schwirz, Jonas; et al. (G3 : Genes, Genomes, Genetics, 2019)
screening approaches.

Calcium supplementation of bioinks reduces shear stress-induced cell damage during bioprinting - Fischer, Lena; Nosratlo, Mojtaba; Hast, Katharina; Karakaya, Emine; Ströhlein, Nadi; Esser, Tilman; Gerum, Richard; Richter, Sebastian; Engel, Felix; Detsch, Rainer; Fabry, Ben; Thievessen, Ingo (Biofabrication, 2022)
During bioprinting, cells are suspended in a viscous bioink and extruded under pressure through small diameter printing needles. The combination of high pressure and small needle diameter exposes cells to considerable shear stress, which can lead to cell damage and death. Approaches to monitor and control shear stress-induced cell damage are currently not well established. To visualize the effects of printing-induced shear stress on plasma membrane integrity, we add FM 1-43 to the bioink, a styryl dye that becomes fluorescent when bound to lipid membranes, such as the cellular plasma membrane. Upon plasma membrane disruption, the dye enters the cell and also stains intracellular membranes. Extrusion of alginate-suspended NIH/3T3 cells through a 200 mu m printing needle led to an increased FM 1-43 incorporation at high pressure, demonstrating that typical shear stresses during bioprinting can transiently damage the plasma membrane. Cell imaging in a microfluidic channel confirmed that FM 1-43 incorporation is caused by cell strain. Notably, high printing pressure also impaired cell survival in bioprinting experiments. Using cell types of different stiffnesses, we find that shear stress-induced cell strain, FM 1-43 incorporation and cell death were reduced in stiffer compared to softer cell types and demonstrate that cell damage and death correlate with shear stress-induced cell deformation. Importantly, supplementation of the suspension medium with physiological concentrations of CaCl2 greatly reduced shear stress-induced cell damage and death but not cell deformation. As the sudden influx of calcium ions is known to induce rapid cellular vesicle exocytosis and subsequent actin polymerization in the cell cortex, we hypothesize that calcium supplementation facilitates the rapid resealing of plasma membrane damage sites. We recommend that bioinks should be routinely supplemented with physiological concentrations of calcium ions to reduce shear stress-induced cell damage and death during extrusion bioprinting.
CRIS-Team WoS Importer:2022-08-26

Phenotypic screen and transcriptomics approach complement each other in functional genomics of defensive stink gland physiology - Lehmann, Sabrina; Atika, Bibi; Grossmann, Daniela; Schmitt-Engel, Christian; Ströhlein, Nadi; Majumdar, Upalparna; Richter, Tobias; Weißkopf, Matthias; Ansari, Salim; Teuscher, Matthias; Hakeemi, Muhammad Salim; Li, Jianwei; et al. (BMC Genomics, 2022)
Background Functional genomics uses unbiased systematic genome-wide gene disruption or analyzes natural variations such as gene expression profiles of different tissues from multicellular organisms to link gene functions to particular phenotypes. Functional genomics approaches are of particular importance to identify large sets of genes that are specifically important for a particular biological process beyond known candidate genes, or when the process has not been studied with genetic methods before. Results Here, we present a large set of genes whose disruption interferes with the function of the odoriferous defensive stink glands of the red flour beetle Tribolium castaneum. This gene set is the result of a large-scale systematic phenotypic screen using RNA interference applied in a genome-wide forward genetics manner. In this first-pass screen, 130 genes were identified, of which 69 genes could be confirmed to cause phenotypic changes in the glands upon knock-down, which vary from necrotic tissue and irregular reservoir size to irregular color or separation of the secreted gland compounds. Gene ontology analysis revealed that many of those genes are encoding enzymes (peptidases and cytochromes P450) as well as proteins involved in membrane trafficking with an enrichment in lysosome and mineral absorption pathways. The knock-down of 13 genes caused specifically a strong reduction of para-benzoquinones in the gland reservoirs, suggesting a specific function in the synthesis of these toxic compounds. Only 14 of the 69 confirmed gland genes are differentially overexpressed in stink gland tissue and thus could have been detected in a transcriptome-based analysis. However, only one out of eight genes identified by a transcriptomics approach known to cause phenotypic changes of the glands upon knock-down was recognized by this phenotypic screen, indicating the limitation of such a non-redundant first-pass screen. Conclusion Our results indicate the importance of combining diverse and independent methodologies to identify genes necessary for the function of a certain biological tissue, as the different approaches do not deliver redundant results but rather complement each other. The presented phenotypic screen together with a transcriptomics approach are now providing a set of close to hundred genes important for odoriferous defensive stink gland physiology in beetles.
CRIS-Team WoS Importer:2022-09-02

TC003132 is essential for the follicle stem cell lineage in telotrophic Tribolium oogenesis - Teuscher, Matthias; Ströhlein, Nadi; Birkenbach, Markus; Schultheis, Dorothea; Schoppmeier, Michael (Frontiers in Zoology, 2017)
BACKGROUND: Stem cells are undifferentiated cells with a potential for self-renewal, which are essential to support normal development and homeostasis. To gain insight into the molecular mechanisms underlying adult stem cell biology and organ evolution, we use the telotrophic ovary of the beetle Tribolium. To this end, we participated in a large-scale RNAi screen in the red flour beetle Tribolium, which identified functions in embryonic and postembryonic development for more than half of the Tribolium genes. RESULTS: We identified TC003132 as candidate gene for the follicle stem cell linage in telotrophic Tribolium oogenesis. TC003132 belongs to the Casein Kinase 2 substrate family (CK2S), which in humans is associated with the proliferative activity of different cancers. Upon TC003132 RNAi, central pre-follicular cells are lost, which results in termination of oogenesis. Given that also Notch-signalling is required to promote the mitotic activity of central pre-follicular cells, we performed epistasis experiments with Notch and cut. In addition, we identified a putative follicle stem cell population by monitoring the mitotic pattern of wild type and TC003132 depleted follicle cells by EdU incorporations. In TC003132 RNAi these putative FSCs cease the expression of differentiation makers and are eventually lost. CONCLUSIONS: TC003132 depleted pre-follicular cells neither react to mitosis or endocycle stimulating signals, suggesting that TC003132 provides competence for differentiation cues. This may resemble the situation in C. elegans were CK2 is required to maintain the balance between proliferation and differentiation in the germ line. Since the earliest effect of TC003132 RNAi is characterized by the loss of putative FSCs, we posit that TC003132 crucially contributes to the proliferation or maintenance of follicle stem cells in the telotrophic Tribolium ovary.
EVALuna2:34601

The iBeetle large-scale RNAi screen reveals gene functions for insect development and physiology - Schmitt-Engel, Christian; Schultheis, Dorothea; Schwirz, Jonas; Ströhlein, Nadi; Troelenberg, Nicole; Majumdar, Upalparna; Dao, Van Anh; Grossmann, Daniela; Richter, Tobias; Tech, Maike; Doenitz, Jurgen; Gerischer, Lizzy; et al. (Nature Communications, 2015)
Genetic screens are powerful tools to identify the genes required for a given biological process. However, for technical reasons, comprehensive screens have been restricted to very few model organisms. Therefore, although deep sequencing is revealing the genes of ever more insect species, the functional studies predominantly focus on candidate genes previously identified in Drosophila, which is biasing research towards conserved gene functions. RNAi screens in other organisms promise to reduce this bias. Here we present the results of the iBeetle screen, a large-scale, unbiased RNAi screen in the red flour beetle, Tribolium castaneum, which identifies gene functions in embryonic and postembryonic development, physiology and cell biology. The utility of Tribolium as a screening platform is demonstrated by the identification of genes involved in insect epithelial adhesion. This work transcends the restrictions of the candidate gene approach and opens fields of research not accessible in Drosophila.

Viscoelastic properties of suspended cells measured with shear flow deformation cytometry - Gerum, Richard; Mirzahossein, Elham; Eroles, Mar; Elsterer, Jennifer; Mainka, Astrid; Bauer, Andreas; Sonntag, Selina; Winterl, Alexander; Bartl, Johannes; Fischer, Lena; Abuhattum, Shada; Goswami, Ruchi; et al. (eLife, 2022)
Numerous cell functions are accompanied by phenotypic changes in viscoelastic prop-erties, and measuring them can help elucidate higher level cellular functions in health and disease. We present a high-throughput, simple and low-cost microfluidic method for quantitatively measuring the elastic (storage) and viscous (loss) modulus of individual cells. Cells are suspended in a high-viscosity fluid and are pumped with high pressure through a 5.8 cm long and 200 µm wide microflu-idic channel. The fluid shear stress induces large, ear ellipsoidal cell deformations. In addition, the flow profile in the channel causes the cells to rotate in a tank-treading manner. From the cell deformation and tank treading frequency, we extract the frequency-dependent viscoelastic cell properties based on a theoretical framework developed by R. Roscoe [1] that describes the deformation of a viscoelastic sphere in a viscous fluid under steady laminar flow. We confirm the accuracy of the method using atomic force microscopy-calibrated polyacrylamide beads and cells. Our measurements demonstrate that suspended cells exhibit power-law, soft glassy rheological behavior that is cell-cycle-dependent and mediated by the physical interplay between the actin filament and intermediate filament networks.
CRIS-Team Scopus Importer:2022-10-28